Pore-scale numerical simulation of spontaneous imbibition in porous media containing fractures - Liu Yang; Xiaoyu Jiang; Mingjun Li; Fei Gong; Guangtao Dong; Xiaoshan Li (Capillarity, 2024)
Spontaneous imbibition is an essential mechanism for recovering oil from low-permeability fractured water-driven reservoirs. To accurately capture the migration interface of oil-water two-phase flow under these conditions, this study employs phase field theory coupled with Cahn-Hilliard and Navier-Stokes equations. We conduct a numerical pore-scale investigation on countercurrent imbibition in low-permeability fractured porous media. The results show that pore-scale spontaneous imbibition can be divided into four stages. In the first stage, oil-water film is formed when oil contacts with water, and this contact line moves under the action of capillary force. In the second stage, the oil film at the end of the oil cluster ruptures to form isolated oil droplets. In the third stage, these oil droplets are surrounded by water and gradually transported outward. In the final stage, oil droplets accumulate in the fractures and are collectively expelled from the matrix. In the process of oil droplet migration, the phenomenon of sticking occurs under the influence of water extrusion and the internal structure of the matrix, which leads to the formation of residual oil. The increased complexity of open boundary and fracture development strengthens the imbibition effect by elevating the degree of spontaneous imbibition pore utilization, thus improving the oil utilization efficiency. The above findings can provide a numerical modeling reference for the study of spontaneous imbibition in fractured porous media, and at the same time, has some guiding significance for the development of low-permeability reservoirs. Document Type: Original article Cited as: Yang, L., Jiang, X., Li, M., Gong, F., Dong, G., Li, X. Pore-scale numerical simulation of spontaneous imbibition in porous media containing fractures. Capillarity, 2024, 10(2): 48-56. https://doi.org/10.46690/capi.2024.02.03